SPE Rocky Mountain Regional Meeting 1997
DOI: 10.2118/38348-ms
|View full text |Cite
|
Sign up to set email alerts
|

Oil Well Stimulation with Hydrogen Peroxide

Abstract: Studies have indicated resources of 4.6 trillion barrels of heavy oil, and some have expressed a need of novel methods to recover some of this oil. Thermal methods were the vogue twenty years ago, with only one method, steam injection, surviving to a significant extent. This paper describes economic uses of hydrogen peroxide, which is similar to steam injection but with some advantages. Hydrogen peroxide can generate 100% quality steam insitu in concentrations above 25–30%. Lesser concentrations can generate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It was also found that the presence of the magnetic field promotes cracking reactions. Moreover, the injection of HP aqueous solutions into the oil reservoirs as a method of heating and enhance oil recovery has been proposed and assessed (Anikin et al, 2022;Bayless and Williams, 1989).…”
Section: Auto-thermal Steam Gasification (Atsg) With Hydrogen Peroxidementioning
confidence: 99%
“…It was also found that the presence of the magnetic field promotes cracking reactions. Moreover, the injection of HP aqueous solutions into the oil reservoirs as a method of heating and enhance oil recovery has been proposed and assessed (Anikin et al, 2022;Bayless and Williams, 1989).…”
Section: Auto-thermal Steam Gasification (Atsg) With Hydrogen Peroxidementioning
confidence: 99%
“…The system forms a foam-like fracturing fluid, which effectively reduces fluid loss, increases pressure, and promotes flowback (Saidu Mohamed 2013;Mitchell et al 1984;Khalil and de Franco 1990). However, the heat-generating agents are reacted based on an acidic environment (Bayless 1997;Bayless 1998Bayless , 2000, but the conventional water-based fracturing fluid system is crosslinked and carries proppant in a slightly alkaline environment. Therefore, it is necessary to use a new type of acid-resistant fracturing fluid system in combination with a heat-generating agent system (Davies et al 1981).…”
Section: Introductionmentioning
confidence: 99%